The cerebellum and cognition: cerebellar lesions impair sequence learning but not conditional visuomotor learning in monkeys. - Nixon, P; Passingham, R (2000)
Claims that the cerebellum contributes to cognitive processing in humans have arisen from both functional neuroimaging and patient studies. These claims challenge traditional theories of cerebellar function that ascribe motor functions to this structure. We trained monkeys to perform both a visuomotor conditional associative learning task and a visually guided sequence task, and studied the effects of bilateral excitotoxic lesions in the lateral cerebellar nuclei. In the first experiment three operated monkeys showed a small impairment in post-operative retention of a visuomotor associative task (A) but were then not impaired in learning a new task (B). However, the impairment on A could have been due to a problem in making the movements themselves. In a second experiment we therefore gave the three control animals a further pre-operative retest on both A and B and then tested after surgery on retention of both tasks. Though again the animals showed motor problems on task A, they reached criterion, and at this stage could clearly make both movements satisfactorily. The critical test was then retention of task B, and they were not impaired. In the final experiment (serial reaction time task) the monkeys response times on a repeating visuomotor sequence were compared with those for a pseudo-random control sequence. After bilateral nuclei lesions they were slow to execute the pre-operatively learned sequence but were still faster on this than on the control task. However, when they were then given a new repeating sequence to learn, they never performed the sequence as quickly as they had on retention of the first sequence. We conclude that the cerebellum is not essential for the learning or recall of stimulus-response associations but that it is crucially involved in the process by which motor sequences become automatic with extended practice.